100k views
5 votes
6x + 7y = 4x + 4y
Complete the missing value in the solution to the equation.
( ?,-4)

User SELA
by
5.1k points

1 Answer

6 votes

Hi there!

»»————- ★ ————-««

I believe your answer is:

(6, -4)


x = 6

»»————- ★ ————-««

Here’s why:

⸻⸻⸻⸻

  • We would need to solve for 'x'. We are already given the 'y' value of '-4', so we would need to substitute y for '-4', and then undo operations to isolate 'x'.

⸻⸻⸻⸻


\rightarrow 6x + 7(-4) =4x + 4(-4)\\\\\rightarrow 6x - 28 = 4x - 16\\\\\rightarrow 6x - 28 + 28 = 4x - 16 + 28\\\\\rightarrow 6x = 4x + 12\\\\\rightarrow 6x - 4x = 4x - 4x + 12\\\\\rightarrow 2x = 12\\\\\rightarrow (2x=12)/(2)\\\\\rightarrow \boxed{x = 6}

⸻⸻⸻⸻

The '6' would replace the question mark.

»»————- ★ ————-««

Hope this helps you. I apologize if it’s incorrect.

User Yizhar
by
5.2k points